2015
DOI: 10.5114/ceji.2015.52835
|View full text |Cite
|
Sign up to set email alerts
|

Review paper Current views on the mechanisms of immune responses to trauma and infection

Abstract: According to the World Health Organization, post-traumatic mortality rates are still very high and show an increasing tendency. Disorders of innate immune response that may increase the risk of serious complications play a key role in the immunological system response to trauma and infection. The mechanism of these disorders is multifactorial and is still poorly understood. The changing concepts of systemic inflammatory response syndrome (SIRS) and compensatory anti-inflammatory response syndrome (CARS) early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 51 publications
1
75
0
3
Order By: Relevance
“…25,[29][30][31] Extensive surgical trauma as well as sepsis lead to a phase of immunosuppression termed compensatory anti-inflammatory response syndrome after an initial proinflammatory state known as systemic inflammatory response syndrome. 32,33 Occurrence of complications might therefore disturb the already delicate postoperative immunological balance in these patients, multiplying the postoperative immunosuppressive state. It has furthermore been demonstrated that HIPEC itself can induce immunosuppression as a result of hematologic toxicity and systemic absorbance of the chemotherapeutics used.…”
Section: Discussionmentioning
confidence: 99%
“…25,[29][30][31] Extensive surgical trauma as well as sepsis lead to a phase of immunosuppression termed compensatory anti-inflammatory response syndrome after an initial proinflammatory state known as systemic inflammatory response syndrome. 32,33 Occurrence of complications might therefore disturb the already delicate postoperative immunological balance in these patients, multiplying the postoperative immunosuppressive state. It has furthermore been demonstrated that HIPEC itself can induce immunosuppression as a result of hematologic toxicity and systemic absorbance of the chemotherapeutics used.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxemia, sepsis, burn injury, and trauma can all lead to a systemic inflammatory response due to excessive activation of the innate immune system (Binkowska et al, 2015; Iskander et al, 2013; Sherwood and Toliver-Kinsky, 2004). The spleen plays a central role in the pathophysiology of the hyperinflammatory state triggered by these threatening conditions, and splenic macrophages are a dominant source of pro-inflammatory cytokines.…”
Section: Impact Of Cholinergic Therapy and α7nachrs In Models Of Smentioning
confidence: 99%
“…Because bacterial infection accounted only for ~10% of the total scoring for adults, the independent risk factors for death from kala-azar in Brazil are causally linked to systemic infl ammation. However, and unfortunately, there is no effective recommendation for treating systemic infl ammation (49) (50) .…”
Section: Tablementioning
confidence: 99%